Islamic literature in modern Indonesia: political disputes among Muslim writers, 1930s-1960s - Sudarnoto Abdul Hakim (IAIN Salatiga, 2023)
This article examines the evolution of Islamic elements in twentieth-century Indonesian literature. The study employs historical analysis and methods to assess the continuity and change in the expression of Islamic themes in literary works. By examining the verses in literary works and the criticism that surrounds them, the article shows that Islamic literature has transformed significantly over the last decade. The article argues that literary criticism among Muslim writers goes beyond literary critique to encompass an assessment of political ideology. Literary works are viewed as a means to address issues such as communist ideology, as well as a medium of da’wah by Muslim writers or poets. As such, the study finds that both Islamic melodramatic and Islamic romance literature has ideological impulses. Overall, the article highlights the importance of examining the intersection of literature and politics, particularly in the context of Islamic literature in Indonesia. By tracing the evolution of Islamic elements in literary works, the study provides valuable insights into the cultural and political history of Indonesia.